Skill Development Policies in India: Implications and Challenges - Harshil Sharma (Journal of Education and Vocational Research, 2018)
India which is moving through ‘demographic dividend’ and wants to achieve tag of ‘knowledge based economy’ need to invest in skill formation and developing educated and skilled workforce. This article will begin by broad overview of education and critical evaluation of current skill development policies at school and vocational level. There would be a brief discussion on role played by private sector in training of workforce in India and what are challenges faced by employers and employees and where lies the conflict of interest. After that in concluding section the major problems will be combined together to come out with the broad basic reason for the failure of such policies and conclude by scrutinizing what can be done in future to bridge the gap between educated and employed. Policy approach to skill development is supply driven and less attention is paid to demand side factors. Study recommends creating national training funds which can be used to collect levies from organized and large firms to be used for skill development of the informal sector. Levy based financing can help in solving problem of free rider and moral hazard as is held by the private sector. Study also recommends making vocational education compulsory from 8th standard and bridging the wide gap that exists in Indian labor market between ‘educated’ and ‘employable’.